Prophet Yusuf (AS) and The King's Dream - "Khan, Saniyasnain" (China; Goodword Books, 2024)
Prophet Yusuf and The King$1 (Bs Dream is a beautifully illustrated board book that introduces young children to one of the most captivating stories from the Quran. Told in simple, gentle language, it shares the moment when Prophet Yusuf (peace be upon him) interprets the king$1 (Bs mysterious dream. The story teaches important values like patience, wisdom, honesty, and faith in Allah. Each page is filled with bright, colorful illustrations that engage little readers and bring the story to life. Designed for toddlers and preschoolers, the sturdy board book is perfect for small hands and repeated reading. This book encourages spiritual growth and early conversations about dreams, faith, and trusting Allah$1 (Bs divine plan.s
Keywords: Prophets Stories